2021
DOI: 10.3389/fpubh.2021.796775
|View full text |Cite
|
Sign up to set email alerts
|

How the Spouse's Retirement Affects the Cognitive Health of Individuals in China: A Fresh Evidence From the Perspective of Social Interaction

Abstract: Background: With the rapid aging of global population, the health consequences of retirement reform are debated greatly. However, most previous studies are limited to the effects on individual themselves, and pay scant attention to the social interaction between individuals and their spouse which may induce the social multiplier effect of retirement. Driven by the practical and academic motives, this study investigates the impacts of the spouse's retirement on the individual's cognitive health among Chinese du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Secondly, personal social networks also significantly affect personal health. Researches have shown that spouse interaction ( 10 ), parents' social status and behavior ( 11 , 12 ), and education level ( 13 ) may have an impact on health. In addition, external factors such as economy, politics, environmental pollution, local culture and education also impact personal health.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, personal social networks also significantly affect personal health. Researches have shown that spouse interaction ( 10 ), parents' social status and behavior ( 11 , 12 ), and education level ( 13 ) may have an impact on health. In addition, external factors such as economy, politics, environmental pollution, local culture and education also impact personal health.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ( 47 ) found that older adults may drink more frequently after retirement due to reduced work restrictions and increased leisure time ( 47 ). However, Zou et al ( 31 ) found that retirement weakens work-related social networks and reduces the probability of drinking ( 30 ). Some research even found that a significant relationship does not exist between retirement and alcohol consumption ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, we restrict the retirement group to individuals who are not working due to retirement to exclude interfering factors, such as the temporary unemployment. This reduces the observations from 100,821 to 83,476; Second, given the government departments, public institutions, state-owned enterprises, and collectively owned enterprises can more strictly implement the statutory retirement system in China ( 30 ), we further excluded samples not in these units ( 30 ). The sample size is reduced to 59,787.…”
Section: Methodsmentioning
confidence: 99%